GLOBALIZATION AND ENGLISH LANGUAGE TEACHING IN INDONESIA - Sutaryo Sutaryo; Komari Komari; Nurprihatina Hasan (FKIP Universitas Khairun, 2021)
This essay discusses the processes of globalization in English language teaching in Indonesia. First, it addresses the status of English language in the world and how English plays its position in Indonesian context within its diverse linguistic background. Second, from the historical perspectives, it discusses the processes of globalization in Indonesian ELT education and curriculum policies both in language pedagogies and teaching materials and how issues and concerns occur. Then, it discusses how the presence of technological advancement in any form facilitatess ELT in Indonesia. All parties in Indonesia including policy makers, educationists, and teachers should should take the most benefits from globalization through maximizing ELT partnership programs both nationally and internationally such as trainings, workshops, and sholarships for further studies. Similarly, the present development of information technology needs to be taken into account for better ELT in Indonesia by providing sufficient funding, particularly from Indonesian government (both central and local) spent for both sustainable ELT human resources development and their supporting facilities. These efforts are very important to enable students to succeed in achieving their communicative competencies in English to be able to survive in global competitiveness.